The child creativity test (TCI) - Sanchez-Ruiz, Maria-Jose (2016)
Divergent thinking tests do not generally address the complex nature of creativity but rather focus on the final product or solution of a problem, overlooking the previous stages of the creative process such as the discovery and formulation of a problem. The present study adopts the lrsquo;problem finding’ model and presents a new measure of creativity in children in primary education (6-12 years old). This paper presents the theoretical foundations as well as the process of designing, developing, and validating the test through different studies. The Child Creativity Test (TCI in Spanish) evaluates the creative process through a task structured in two stages: formulation and solution of a problem. The test considers not only the final output (a drawing), but also the previous phases that lead to it. Results show satisfactory validity and reliability of the test scores. It is concluded that the TCI has robust psychometric properties and can be a useful tool to predict creative behavior in primary school children.